Multimodal Analysis of Mie Sedaap Advertising - Meriantini, Ni Luh (Jurnal Pendidikan Bahasa Inggris undiksha, 2023)
One of the texts has a complex meaning is advertisement, both print media advertisements and electronic media advertisements. The complexity of meaning is due to conveying messages in advertisements not only using language elements but also nonverbal language elements and other visual means. Therefore to understand the complexity of meaning, it is necessary to carry out a multimodal analysis in the advertisement. This study aims to analysis of Mie Sedaap advertisements. Advertisements, both print media advertisements and electronic media advertisements, are texts that have a complex meaning. Therefore, to understand the complexity of meaning, it is necessary to do a multimodal analysis of the advertisement. The multimodal analysis discussed in this paper uses the theory of Systemic Functional Linguistics (SFL). This study used a descriptive qualitative method and observation through video advertisements for Mie Sedaap. The data were collected from observations through video advertisements for Mie Sedaap. The findings of the study were analyzed using qualitative data analysis, including data reduction, data display, and conclusion. The research results show that Mie Sedaap advertisements have a multimodal semiotic system that includes linguistic, visual, audio, gestural, and spatial elements.